Urban decentralisation - Sethi, J.D
The author discusses the need for the urban decentralisation and redefines some of its aspects. It is argued that the urban decentralisation would help in planned expansion of tiny and small units located in a manner that would provide maximum employment. The decentralisation of economic activities would change the character of the informal sector. The urban areas can be safe for living if proper infrastructure facilities are made available. But there is need for the development of local initiatives for the genuine decentralisation.
Keywords: Urban Decentralisation; Decentralisation; Municipal Government - India